Otimização de biodegradação de querosene em água do mar por Candida lipolytica UCP 0988. - Correia, Maria Andreza Bezerra (2014)
Activities of oil refineries and accidental spills with oil and derivatives release in the environment highly toxic hydrocarbons, that represent a great danger, especially for communities near of the contaminated site. Central Composite Design - associated with the Response Surface Methodology- was carried out to optimize the degradation of kerosene by Candida lipolytica UCP 0988 in hypersaline and highly alkaline seawater The seawater was collected in beach near the Porto de Suape, Pernambuco, Brazil . Illuminating kerosene was used as sole carbon source in biodegradation assays, conducted for 15 days, at 28°C, in shake flasks at 200 rpm. Mass concentration, surface tension, pH and salinity were used as indirect indicators of biodegradation of kerosene. The yeast C. lipolytica UCP 0988 showed ability to grow in sea water using kerosene as the sole carbon source under extreme alkaline and saline stress. Predictive models for response variables surface tension, pH and salinity as a function of the ammonium sulfate and potassium phosphate monobasic concentrations were obtained by regression analysis. Analysis of variance was used to evaluate the significance and precision of the models. Determination coefficients respectively equal to 91, 98 and 80% were obtained for the models of surface tension, pH and salinity. The p values were less than 0.05 for surface tension and pH and less than 0.10 for salinity. The relative deviations between the experimental results and the model predictions were less than 2.2% for surface tension and salinity and less than 6% for pH. The results indicate that the haloalkalitolerant yeast C.lipolytica UCP 0988 and its bioproducts (buiosurfactants /bioemulsifiers) may be useful for theoretical and experimental researches on multiple tolerance mechanisms and bioremediation of oil and oil products, such as kerosene, in seawater.